Dilution of oral D(3)‐Creatine to measure creatine pool size and estimate skeletal muscle mass: development of a correction algorithm - Shankaran, Mahalakshmi (J Cachexia Sarcopenia Muscle, 2018)
BACKGROUND: Muscle mass can be measured directly in vivo by isotope dilution, using Creatine‐(methyl‐d(3)) monohydrate (D(3)‐Cr) by mouth followed by measurement of the steady‐state enrichment of D(3)‐creatinine (D(3)‐Crn) in urine. Isotope dilution methods require knowledge of the amount of tracer delivered to the pool of interest. In a subset of human subjects, a small amount of orally administered D(3)‐Cr ‘spills’ into urine after absorption and prior to transport into skeletal muscle cells. The objectives were to develop a method to correct for spillage to compare the estimate of muscle mass by D(3)‐Cr dilution to other assessments of fat‐free mass. METHODS: Subjects (19 males, 23–81 years old; 20 females, 20–77 years old) ingested a single dose of 60 mg D(3)‐Cr and urine was collected prior to and daily for 4 days following the dose. Fasting morning urine samples was assessed for D(3)‐Cr, total Cr, D(3)‐Crn, and total Crn concentrations, as well as isotopic enrichments of D(3)‐Crn, by LC/MS. The 24‐h urine collections over 3 days after the dose of D(3)‐Cr were also performed to determine D(3)‐Cr spillage. Total body water, fat mass, and fat‐free mass were assessed by bioelectrical impedance spectroscopy (BIS). RESULTS: Spillage of D(3)‐Cr in the urine was greater in women than men. D(3)‐Crn enrichment and the ratio of Cr/Crn were used in an algorithm to calculate Cr pool size and muscle mass. Specifically, an algorithm was developed for the estimation of spillage based on the relationship between the fasting Cr/Crn ratio and the cumulative proportion of the D(3)‐Cr dose excreted over 3 days based on 24‐h urine collections. Muscle mass corrected using the algorithm based on fasting urine levels correlated (r = 0.9967, P < 0.0001) with that corrected by measuring D(3)‐Cr dose excreted. Muscle mass measured by D(3)‐Crn enrichment also correlated (r = 0.8579, P < 0.0001, algorithm corrected) with that measured by 24‐h Crn excretion. Muscle mass measured by D(3)‐Cr dilution method correlated with intracellular water by BIS, whether using spillage corrected by the algorithm (r = 0.9041, P < 0.0001) or measured by 3 day D(3)‐Cr losses (r = 0.91, P < 0.0001) and similarly correlated with fat‐free mass by BIA (r = 0.8857 and 0.8929, P < 0.0001, respectively). CONCLUSIONS: The D(3)‐Cr dilution method is further validated here as a non‐invasive, easy‐to‐use test for measuring muscle mass. The technical issue of D(3)‐Cr spillage can be corrected for with a simple algorithm based on fasting spot urine samples. Muscle mass by Cr dilution potentially has broad applications in clinical and research settings.